COMPUTATIONAL ANALYSIS OF MUTATIONS IN REALLY INTERESTING NEW GENE FINGER DOMAIN AND BRCA1 C TERMINUS DOMAIN OF BREAST CANCER SUSCEPTIBILITY GENE - SABITHA, KESAVAN; Kodous, Ahmad; Rajkumar, Thangarajan (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Breast Cancer 1 (BRCA1), Early Onset and Breast Cancer 2, Early Onset (BRCA2) genes are involved in pathways important for DNA damage recognition, double-strand break repair, checkpoint control, transcription regulation, and chromatin remodeling. These functions are essential and important for all cell types. Germline mutations in these genes increase the risk of breast and ovarian cancer in women. In this study, we did an analysis of the functional and structural impact of all known single nucleotide polymorphisms (SNPs) in BRCA1 and BRCA2 using publicly available computational prediction tools. Methods: We analyzed the mutations using two mutation tolerance prediction approaches: Sorting intolerant from tolerant (SIFT), and polymorphism phenotyping (PolyPhen-2). In addition, stability of the protein was analyzed by I-Mutant. Affinity and stability of really interesting new gene (RING) and BRCA1 C-terminus (BRCT) domains were also analyzed by BioLuminate tool. Results: Out of 486 SNPs in BRCA retrieved from functional SNP, a total of 10 SNPs were found to be deleterious by SIFT and PolyPhen. I-Mutant results indicate that C27F, A1708V could increase the stability of protein, whereas other mutations decrease the stability. Predicted changes in stability and affinity of RING and BRCT domains of BRCA were computed using residue scanning functionality in bioluminate for all 10 SNPs. The mutation C61R could affect the stability of RING domain and all mutations in BRCT domain were affecting the inter subunit affinity and stability of the complex. Conclusion: The combination of computational methods provides a way in understanding the impact of deleterious mutations in altering the BRCA protein stability and affinity. Based on our investigation, we report potential candidate SNPs for future studies of BRCA mutations. Keywords: Breast cancer susceptibility gene, BRCA1 C terminus domain, Zinc finger domain, Sorting intolerant from tolerant, Polymorphism phenotyping, I-mutant, BioLuminate.